THE MACROECONOMIC DETERMINANTS OF POLITICAL STABILITY IN TRANSITION ECONOMIES AFTER COLLAPSE OF SOVIET UNION - Bayat, Tayfur; Kişman, Zülfükar Aytaç; Tasar, İzzet (My University, 2018)
The successful integration of the post-Soviet countries to European Union and to other market economies via economic and political transition has been a substantial issue for international economic and political relations. Amid all the structural changes it has been of significant importance for the policy makers to set forth the macroeconomic determinants of the political stability in transition economies moved from centrally planned economy through market economy. In this study the macroeconomic determinants of the political stability within the transition economies between 2002-2015 have been investigated by utilizing the panel data method. Depending on the empirical analysis, it has been concluded that GDP per capita and consumer price index are the most important macroeconomic factors affecting the political stability in the short-term.
Keywords: Siyasi Bilimler; İktisat